Delayed-onset hearing loss in first-grade students who previously passed the newborn hearing screening - Elbeltagy, Reem; AlObayed, Waad; Mashbri, Shatha; Alrasheed, Robina; Albakiri, Renad; Almulayfi, Munira; Alkahtani, Rania (Frontiers in Pediatrics, 2025)
IntroductionNewborn hearing screening is essential for the early detection of hearing loss, enabling timely intervention that supports communication and academic success. However, some children may develop delayed-onset hearing loss, which can go undetected without ongoing monitoring. Even mild hearing loss can affect educational development, highlighting the importance of preschool hearing screening. This study aimed to investigate the prevalence of delayed-onset hearing loss in first-grade students who had previously passed newborn hearing screening, emphasizing the need for early identification.MethodsA cross-sectional study was conducted involving 130 first-grade students. The screening protocol included otoscopic examination, Pure Tone Audiometry (PTA), tympanometry, and Transient Evoked Otoacoustic Emissions (TEOAE). Passing criteria were defined as PTA thresholds ≤20 dBHL at 500–4,000 Hz, Type A or Ad tympanogram, and a TEOAE signal-to-noise ratio ≥3 dB.ResultsOf the participants, 80 (61.5%) passed the hearing screening, while 50 (38.5%) failed. Among those who failed, 43 (86%) showed abnormal tympanometry results, indicating potential conductive hearing loss, whereas 7 (14%) failed both OAE and PTA despite having normal tympanometry and were confirmed to have sensorineural hearing loss (SNHL). The prevalence of delayed-onset SNHL was therefore 5.4%. Among the risk factors examined, consanguinity was significantly associated with the presence of hearing loss.ConclusionThe observed 5.4% prevalence of delayed-onset sensorineural hearing loss among first-grade students underscores the importance of implementing preschool hearing screening to ensure early detection and timely intervention.